2003
DOI: 10.1002/ange.200352102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Oligonucleotides Containing the C4′‐Oxidized Abasic Site Produced by Bleomycin and Other DNA Damaging Agents

Abstract: Exposure of DNA to oxidative stress produces strand scission and a variety of damaged nucleotides, which can be mutagenic and/or cytotoxic. The determination of the effects of specific lesions on nucleic acid structure, stability, and their interaction with polymerase and repair enzymes provide a chemical basis for the biological effects of DNA damage. [1,2]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 35 publications
2
36
0
Order By: Relevance
“…To obtain an oligonucleotide containing a 2-deoxyribose (LysA30-AP), LysA30-U was treated with an excess amount of uracil DNA glycosylase as described previously (35). LysA30-L contained a 2-deoxyribonolactone (L) and was prepared by UV irradiation (350 nm) of parental oligonucleotide containing the appropriate photochemical precursors (36,37). Figure 1 shows the structures of these various abasic sites.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain an oligonucleotide containing a 2-deoxyribose (LysA30-AP), LysA30-U was treated with an excess amount of uracil DNA glycosylase as described previously (35). LysA30-L contained a 2-deoxyribonolactone (L) and was prepared by UV irradiation (350 nm) of parental oligonucleotide containing the appropriate photochemical precursors (36,37). Figure 1 shows the structures of these various abasic sites.…”
Section: Methodsmentioning
confidence: 99%
“…C4-AP undergoes strand scission in free DNA under physiologically relevant buffer conditions considerably more rapidly than AP. 38,5557…”
Section: Resultsmentioning
confidence: 99%
“…C4-AP, DOB, and AP photochemical precursor phosphoramidites were synthesized as described previously and incorporated into DNA by solid phase oligonucleotide synthesis. 13,37,38 [γ-32 P]dATP and [α-32 P]ATP (cordycepin) were obtained from PerkinElmer. Protein purification was conducted using an AKTA FPLC instrument using columns from GE Healthcare.…”
mentioning
confidence: 99%
“…22,23 In spite of the possible advantages of amine modification, one concern is that the 1,4-dicarbonyl system in 3 could undergo strand cleavage at the β-position of the aldehyde (β-elimination) during the bioconjugation; this would generate ODN fragments that are unsuitable for conjugation. Leumann reported that the strand cleavage of abasic RNA sites and their 2′-O-methylated analogs under alkaline conditions was slower than that observed with abasic DNA.…”
Section: Bioconjugation Of Oligodeoxynucleotides (Odns) With Biomolecmentioning
confidence: 99%